2000
DOI: 10.1046/j.1442-2018.2000.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among conflict, conflict management, job satisfaction, intent to stay, and turnover of professional nurses in Thailand*

Abstract: This study was conducted to describe level of conflict, conflict management styles, level of job satisfaction, and intent to stay, and to ascertain relationships among conflict, conflict management styles, level of job satisfaction, intent to stay, and turnover of professional nurses in Thailand. The sample was 354 professional nurses employed in four regional hospitals in Thailand. The findings showed that the overall level of conflict was at a moderate level. The majority of subjects used accommodation most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 21 publications
4
61
0
2
Order By: Relevance
“…The present study had three limitations. First, our questionnaire did not include socioeconomic status and psychological factors related to turnover which were suggested by previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , that is, parental or children care demands, salary level, social support, job demand, and job discretion. Secondly, we were unable to collect the reasons for the turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study had three limitations. First, our questionnaire did not include socioeconomic status and psychological factors related to turnover which were suggested by previous studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] , that is, parental or children care demands, salary level, social support, job demand, and job discretion. Secondly, we were unable to collect the reasons for the turnover.…”
Section: Discussionmentioning
confidence: 99%
“…It can cause decreases in numbers of high-skilled nurses and has an adverse impact on the nursing department, the hospital environment, and the quality of care in medical institutions 1,2) , as well as incurring high costs 3) . Many studies have explored the factors affecting nurses' turnover and their intention of leaving [1][2][3][4][5][6][7][8][9][10][11][12] . They have indicated that the factors affecting intention of leaving were low job satisfaction, inadequacy of staffing, poor salary and welfare, high job stress, low group cohesion, weak leadership by superiors, and work schedule.…”
mentioning
confidence: 99%
“…(25) işi iyi olan, gelir düzeyi iyi olan ve değişik işlerde çalı-şanlarda iş doyumu yüksek saptamıştır. Ülkemizde ve yurt dı-şında hemşirelerde yapılan araştırmalarda da benzer sonuçlar bulunmuştur (26). Kıbrıs Yakındoğu Üniversitesi ve Fırat Üni-versitesi akademik personellerinde çalışmalarda iş doyumu ile gelir düzeyleri arasında ilişki saptanmamıştır.…”
Section: Discussionunclassified
“…(Barki H. a., 2004) However it is defined , conflict is an accepted part of daily and work life. Kunaviktikul et al (2000) describe conflict as "natural and inevitable", but if we can reduce any of the three perceived properties, interference, negative emotion or disagreement, we can decrease overall conflict in that setting.…”
Section: Definition Of Conflictmentioning
confidence: 99%
“…In general it is important to remember, however, that avoiding the issue never resolves it; it only prolongs the inevitable confrontation (McElhaney, 1996). The primary conflict strategies of many nurses are avoidance and obliging (Kunaviktikul, Nuntasupawat, Srisuphan, & Booth, 2000) with avoidance being more common in younger nurses (Iglesias & Becerra de Bengoa Vallejo, 2012). …”
Section: A Voiding Stylementioning
confidence: 99%